Balkan perspectives of Europe
1 online resource
Keywords: Through the lens of the Balkan nations, this volume makes a valuable and significant contribution to the fields of European and Southeast European studies by reconsidering the East/West dichotomy - both in terms of the Orient-Occident divide and the Eastern-Western Europe binary.Balkan Perspectives of Europe focuses on concepts of Europe as articulated in the Balkans from the nineteenth century to the present - an area that remains largely underexplored, despite extensive research on national identity and the construction of the Other. The authors address this scholarly gap through meticulous bibliographic research, drawing on both published and unpublished sources in Balkan languages. A key strength of the collection is its inclusion of contributors from the Balkans as well as from wider European and American academic contexts, enabling a nuanced and comprehensive examination of the subject through internal and external perspectives. The authors argue that, in asserting their cultural identification with Europe, Balkan nations have developed concepts of Europe that resonate with Occidental discourses and offer a counter-narrative to dominant Western conceptualizations of the Balkans.Broadening access to these ideas, this book's approach allows scholars, students, and general readers to deepen their understanding of the Balkan region and its perspectives on identity and otherness.